The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1623/hysj.53.4.754
|View full text |Cite
|
Sign up to set email alerts
|

Global projections of changing risks of floods and droughts in a changing climate

Abstract: Simulated daily discharge derived from a relatively high-resolution (approximately 1.1-degree) general circulation model was used to investigate future projections of extremes in river discharge under global warming. The frequency of floods was projected to increase over many regions, except those including North America and central to western Eurasia. The drought frequency was projected to increase globally, while regions such as northern high latitudes, eastern Australia, and eastern Eurasia showed a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
250
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 373 publications
(274 citation statements)
references
References 28 publications
10
250
0
3
Order By: Relevance
“…Forzieri et al (2014) project an increase in deficit volume of river flow for vast areas of Europe, except the Scandinavian countries and North Russia. Hirabayashi et al (2008) and Feyen and Dankers (2009) project a substantial increase in the number of drought days (PDY) or flow deficit volume for the period 2071-2100 in some regions, whereas in contrast, wide areas will benefit from a decrease in drought days. An increase in number of drought days in general is not in line with the modelling experiment in this study, whereas an increase in deficit volume is supported (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Forzieri et al (2014) project an increase in deficit volume of river flow for vast areas of Europe, except the Scandinavian countries and North Russia. Hirabayashi et al (2008) and Feyen and Dankers (2009) project a substantial increase in the number of drought days (PDY) or flow deficit volume for the period 2071-2100 in some regions, whereas in contrast, wide areas will benefit from a decrease in drought days. An increase in number of drought days in general is not in line with the modelling experiment in this study, whereas an increase in deficit volume is supported (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The focus on the 100-year event enables a direct comparison with other studies (Lehner et al 2006;Hirabayashi et al 2008;Dankers and Feyen 2009). …”
Section: Flood Frequencymentioning
confidence: 99%
“…Bell et al 2007;Prudhomme et al 2003;Milly et al 2002;Lehner et al 2006;Hirabayashi et al 2008;Dankers and Feyen 2009;Dankers et al 2013). A key conclusion of such studies is that the projected effects of climate change on the flood hazard may be very substantial, but are very dependent on climate scenario.…”
mentioning
confidence: 99%
“…Dankers and Feyen (2008) and Hirabayashi et al (2008) indicated a decrease in water flow, whereas Lehner et al (2006) suggested an increase, and Arheimer et al (2012) projected very little overall change in water discharge to the Baltic Sea. Discrepancies between conclusions regarding the future can arise due to uncertainties in GCMs, downscaling methods, or hydrological models (e.g., Bosshard et al, 2013;Donnelly et al, 2014;Hall et al, 2014).…”
Section: Changes In High Flows In Swedenmentioning
confidence: 99%